Low Complication Rates Using Closed-Incision Negative-Pressure Therapy for Panniculectomies: A Single-Surgeon, Retrospective, Uncontrolled Case Series. Issue 2 (August 2020) - Patel, Ashraf A.; Wilcox, Kailyn; Bhinder, Jasmine; Reiser, Julia; Upadhyaya, Prashant
Abstract : Background: Panniculectomies are associated with high complication rates (43 to 70 percent), particularly in patients with obesity, smoking, and diabetes mellitus. Closed-incision negative-pressure therapy can be used postoperatively to support healing by promoting angiogenesis and decreasing tension. The authors hypothesized that using it with panniculectomies would minimize complications, and that a longer duration of therapy would not increase the incidence of complications. The authors also evaluated whether closed-incision negative-pressure therapy malfunction was associated with complications. Methods: This retrospective, uncontrolled case series analyzed 91 patients who underwent panniculectomies managed with closed-incision negative-pressure therapy performed by a single surgeon from 2014 to 2018. Patients were followed for 6 months; therapy duration and malfunction were recorded. Patients were placed into therapy duration groups (2 to 7, 8 to 10, or >10 days). Complications managed conservatively were minor and major if they required intervention. Odds ratios were performed with 95 percent confidence intervals and p values. Results: Mean follow-up was 225.1 days and mean closed-incision negative-pressure therapy duration was 10.5 days. Major complications were reported in five patients (5.5 percent), infections in four (4.4 percent), dehiscence in two (2.2 percent), and seroma in four (4.4 percent). Patients with malfunction [ n = 16 (17.6 percent)] were more likely to experience complications (OR, 3.3; p = 0.043). No significant increase in complications was found with therapy duration longer than 10 days, but potentially there is an increased risk of infection (OR, 4.0; p = 0.067). Conclusions: Although high complication rates have been associated with panniculectomies, the authors' results show that low complication rates can be achieved with closed-incision negative-pressure therapy. Randomized controlled trials need to be conducted evaluating different therapy systems and the optimal duration of therapy with panniculectomies. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.